Photoprotection Knowledge and Photoprotective Behavior of University Students: A Cross-sectional Study in Indonesia - Regina Stefani Roren; Paulus Mario Christopher; Nana Novia Jayadi (Wolters Kluwer Health, 2022)
Objective:. Awareness regarding the negative effects of ultraviolet radiation are commonly neglected in Asian countries. This study sought to evaluate the ultraviolet radiation knowledge and photoprotective behaviors of university students in Indonesia. Methods:. This observational cross-sectional was conducted at Pelita Harapan University, Indonesia. Results:. A total of 89 (45.4%) medical students and 107 (54.6%) nonmedical students participated in this study. Their mean age was 21.03 ± 2.03 years, and 46.4% of them had Fitzpatrick type III skin. Medical students as well as older students exhibited a higher level of knowledge regarding photoprotection (P ≤ 0.05). Factors related to good photoprotective behaviors were sex, older age, and average expenditure on skincare. Further analysis revealed that a high level of knowledge regarding photoprotection was related to acceptable photoprotective behaviors (P = 0.01; odds ratio = 1.97; 95% confidence interval = 1.13-3.54). Conclusions:. Knowledge regarding sun-related damage and practice of photoprotective behaviors were low among the participants. The results indicate that formal education and academic subjects should incorporate the topic of sun-related damage and promote the practice of photoprotective behaviors early on to increase awareness among populations.